Economic governance of MFIs: Inside the black box - Thankom Arun; Samuel Kobina Annim (Institute for the Study of Labor (IZA), 2010)
This paper investigates a relationship between economic governance and the dual objectives of Microfinance Institutions (MFIs): poverty reduction and financial viability. Using an unbalanced panel of 531 MFIs the important role of other institutions such as country-level business registry departments in facilitating targeting of poor clients is illuminated. Comparing the estimates of Hausman-Taylor and Fixed Effects Vector Decomposition allows us to scrutinize and at least partially correct the effects of both time invariant and slow changing endogenous variables. We find that credit information availability and lesser time in securing property enhances the chances of MFIs in achieving their poverty reduction objective. Product diversification leading to economies of scope also enables MFIs to reach poor clients. On the basis of the above, it is imperative for government and development partners to channel their efforts towards provision of an enabling atmosphere that will enhance the achievement of microfinance social objectives.
Keywords: G21; G39; L20; 330; microfinance; dual objectives; economic governance; property rights; credit information; Mikrofinanz; Corporate Governance; Betriebswirtschaftliches Ziel; Armutspolitik; Schätzung; Welt